The role of Weizmannia (Bacillus) coagulans LMG S-31876 in treating IBS-diarrhea - Kallur, Ranjith Kumar; Madapati, Sreenadh; Mathur, Ankita; Bhattacharya, Sourish (Frontiers in Nutrition, 2024)
Introduction Irritable bowel syndrome (IBS) is a common gastrointestinal condition. Some studies have shown the efficacy of probiotics in the treatment of irritable bowel syndrome (IBS). Weizmannia (Bacillus) coagulans LMG S-31876 has been marketed as a dietary ingredient, but to date, its efficacy in diarrhea-predominant irritable bowel syndrome (IBS) condition has not been clinically elucidated. Thus, a double-blind placebo-controlled multi-centered trial was planned to evaluate the safety and efficacy of Weizmannia (Bacillus) coagulans LMG S-31876 in diarrhea-predominant IBS patients. Experimental design Study participants (n = 50) diagnosed with IBS prominent symptoms that include abdominal pain and other GI-related symptoms were treated with ProBC Plus (2 billion CFU) along with a placebo capsule once daily for approximately 8 weeks. Study participants were evaluated for the treatment success determined by the differences in stool consistency and frequency per day between the intervention and placebo groups over the study period. Results The vital signs and the biochemistry parameters were under the normal range; the other parameters showed a significant result as compared to the placebo during the study period. Conclusion This study depicts a significant decline in the clinical symptoms such as abdominal pain, bloating, diarrhea, and frequency of the stool as compared to the placebo. All the parameters such as hematology, lipid profile, and vital signs were in the normal range during the supplementation of ProBC Plus for a period of 8 weeks. Furthermore, the study verified that Weizmannia (Bacillus) coagulans LMG S-31876 and its probiotic product ProBC Plus at a dose of 2 billion/CFU/day has a prominent action in the relief from the clinical symptoms of IBS-D. Therefore, the product is intended safe to utilize for IBS-related symptoms. Clinical trial registration: The clinical study has been registered with CTRI/2023/01/048644 with https://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=77708&EncHid=24313.96864&userName=CTRI/2023/01/048644 [CTRI/2023/01/048644].